THE RELEVANCE OF PREDICTING RHEUMATHOID ARTHRITIS SEVERITY: FACILITATING EARLY TREATMENT IN POOR PROGNOSIS AND PROGNOSTIC LABORATORY MARKERS OF JOINT DAMAGE - Spasovski, Dejan; Sandevska, Emilija; Pivkova-Veljanovska, Aleksandra; Balkanov, Svetlana Krstevska; Subevska-Stratrova, Slavica (Journal of Morphological Sciences, 2021)
Simultaneous testing especially of erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and rheumatoid factor (RF), which are reversible measures of inflammation, together with clinical variables of inflammatory synovitis are recommended for evaluation of disease activity. In this study 35 patients (pts) with early RA were included, while 35 pts were in the healthy control group. Pts were treated with Methotrexate at an average dose of 10 mg once weekly. RA was evaluated following the dynamics of changes of the mean values of ESR, CRP and RF. Statistical analysis showed statistically significant differences among mean values of ESR in the four time intervals (p=0.00002). Regarding CRP, there were statistically significant differences among mean values in all four time intervals (p=0.0428) (standard deviations were with great variations). There were no statistically significant differences of RF in the four time intervals (p=0.573). We found high values of CRP and RF in most of the patients. In spite of the therapy with Methotrexate, disease progression continues especially in patients with elevated values of ESR, CRP and RF, which are shown as predictors for aggressive course of disease. This enables selection of high risk groups of patients for aggressive course of disease and points to the need of early and aggressive treatment. Keywords: rheumatoid arthritis, reactants of the acute phase, rheumatoid factor https://doi.org/10.55302/JMS2142019s